1999
DOI: 10.1557/proc-565-173
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Copper Penetration in Low-κ Polymer Dielectrics by Bias-Temperature Stress

Abstract: The industry is strongly interested in integrating low-κ dielectrics with Damascene copper. Otherwise, with conventional materials, interconnects cannot continue to scale without limiting circuit performance. Integration of copper wiring with silicon dioxide (oxide) requires barrier encapsulation since copper drifts readily in oxide. An important aspect of integrating copper wiring with low-κ dielectrics is the drift behavior of copper ions in these dielectrics, which will directly impact the barrier requireme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The transport of copper in SiLK film under high electric field bias has been characterized. [15] Figure 5 shows the dependence of copper drift rate in SiLK film with a 1.0 MV/cm applied field as a function of temperature. The rate of transport falls roughly midway between the rate in Si 3 N 4 , considered a copper barrier, and SiO 2 .…”
Section: Copper Driftmentioning
confidence: 99%
“…The transport of copper in SiLK film under high electric field bias has been characterized. [15] Figure 5 shows the dependence of copper drift rate in SiLK film with a 1.0 MV/cm applied field as a function of temperature. The rate of transport falls roughly midway between the rate in Si 3 N 4 , considered a copper barrier, and SiO 2 .…”
Section: Copper Driftmentioning
confidence: 99%
“…Cu can be used without barriers in polymers, taking advantage of process efficiency and a simple structure. [ 42 ]…”
Section: A Contender: Cu/polymer Hybrid Bondingmentioning
confidence: 99%
“…Integration of copper wiring with silicon dioxide (oxide) requires barrier encapsulation since copper drifts readily in the oxide. Loke et al [71] evaluated and compared the copper drift properties in six low-κ organic polymer dielectrics: parylene-F; benzocyclobutene; fluorinated polyimide; an aromatic hydrocarbon; and two varieties of poly(arylene ether).Copper/oxide/polymer/oxide/silicon capacitors subjected to biastemperature stress to accelerate penetration of copper from the gate electrode into the polymer. The study showed that copper ions drifted readily into fluorinated polyimide and poly(arylene ether), more slowly into parylene-F, and even more slowly into benzocyclobutene.…”
Section: Polyimide (Pi)/cupper (Cu) Based Applicationsmentioning
confidence: 99%